Crossed and Linked Histories of Tetrapyrrolic Macrocycles and Their Use for Engineering Pores within Sol-Gel Matrices - Miguel A. García-Sánchez; Fernando Rojas-González; E. Carmina Menchaca-Campos; Salvador R. Tello-Solís; R. Iris Y. Quiroz-Segoviano; Luis A. Diaz-Alejo; Eduardo Salas-Bañales; Antonio Campero (Molecules, 2013)
The crossed and linked histories of tetrapyrrolic macrocycles, interwoven with new research discoveries, suggest that Nature has found in these structures a way to ensure the continuity of life. For diverse applications porphyrins or phthalocyanines must be trapped inside solid networks, but due to their nature, these compounds cannot be introduced by thermal diffusion; the sol-gel method makes possible this insertion through a soft chemical process. The methodologies for trapping or bonding macrocycles inside pristine or organo-modified silica or inside ZrO2 xerogels were developed by using phthalocyanines and porphyrins as molecular probes. The sizes of the pores formed depend on the structure, the cation nature, and the identities and positions of peripheral substituents of the macrocycle. The interactions of the macrocyclic molecule and surface Si-OH groups inhibit the efficient displaying of the macrocycle properties and to avoid this undesirable event, strategies such as situating the macrocycle far from the pore walls or to exchange the Si-OH species by alkyl or aryl groups have been proposed. Spectroscopic properties are better preserved when long unions are established between the macrocycle and the pore walls, or when oligomeric macrocyclic species are trapped inside each pore. When macrocycles are trapped inside organo-modified silica, their properties result similar to those displayed in solution and their intensities depend on the length of the alkyl chain attached to the matrix. These results support the prospect of tuning up the pore size, surface area, and polarity inside the pore cavities in order to prepare efficient catalytic, optical, sensoring, and medical systems. The most important feature is that research would confirm again that tetrapyrrolic macrocycles can help in the development of the authentic pore engineering in materials science.